THE EFFECT OF LINGZHI (Ganoderma lucidum) EXTRACT ADDITION ON ANTIOXIDANT ACTIVITY OF HAND AND BODY LOTION FORMULATIONS - Fitria, Faizatul; Hidayat, Fahmi; Rosanti, Aulia Dewi; Sa’diyah, Asvikatus (Program Studi Pendidikan Kimia, FKIP, Universitas Pattimura (Chemistry Education Study Program, Faculty of Teacher Training and Educational Sciences, Pattimura University), 2024)
Ganoderma lucidum, lingzhi or reishi mushroom is a plant containing secondary metabolites that are of wide interest due to their biological activities. Among them the most important is its Antioxidant activity. Free radicals are potentially damaging byproducts of metabolism. Antioxidants neutralize free radicals in the body and thus help to protect against disease (source) The study was conducted to determine the antioxidant effect, as measured by DPPH radicals scavenging capability of hand and body lotions with lingzhi mushroom extract included. Maceration was used to extract lingzhi and the yield of extraction is 14.17% The results of the preliminary phytochemical analysis showed that lingzhi has contained compounds related to flavonoid, phenolat, triterpenoid and steroid. The antioxidant activity assay further confirmed the results as lingzhi extract showed very high antioxidant (46.9 ppm) potential when tested against DPPH scavenging by abrogating red purple color at 517nm table(Table.). In addition, the incorporation of lingzhi extract with hand and body lotion also increased antioxidant activity, where 0.75% lingzhi extract was found have to produce most effective DPPH inhibition [IC50 = 28.47 ppm].